Global Asymptotic Stability of Solutions to Nonlinear Marine Riser Equation. (15th September 2010) - Gür, Şevket
Abstract : This paper studies initial boundary value problem of fourth-order nonlinear marine riser equation. By using multiplier method, it is proven that the zero solution of the problem is globally asymptotically stable.